The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/art.37806
|View full text |Cite
|
Sign up to set email alerts
|

Loss of methylation in CpG sites in the NF‐κB enhancer elements of inducible nitric oxide synthase is responsible for gene induction in human articular chondrocytes

Abstract: Objective To investigate whether the abnormal expression of inducible nitric oxide synthase (iNOS) by osteoarthritic (OA) human chondrocytes is associated with changes in the DNA methylation status in the promoter and/or enhancer elements of iNOS. Methods Expression of iNOS was quantified by quantitative reverse transcriptase–polymerase chain reaction. The DNA methylation status of the iNOS promoter and enhancer regions was determined by bisulfite sequencing or pyrosequencing. The effect of CpG methylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 51 publications
(65 reference statements)
5
64
2
Order By: Relevance
“…This is contrary to our recent findings on the NOS2 enhancer (14) and MMP13 promoter (15). It is possible that in the absence of differential methylation, the increased expression of COL2A1 observed in OA chondrocytes could be explained by the regenerative efforts of the cells to restore the ECM as an anabolic response within a degradative environment.…”
Section: Discussioncontrasting
confidence: 99%
“…This is contrary to our recent findings on the NOS2 enhancer (14) and MMP13 promoter (15). It is possible that in the absence of differential methylation, the increased expression of COL2A1 observed in OA chondrocytes could be explained by the regenerative efforts of the cells to restore the ECM as an anabolic response within a degradative environment.…”
Section: Discussioncontrasting
confidence: 99%
“…Another gene which is found to be associated with catabolic activity in cartilage is the inducible nitric oxide synthase (iNOS). The association between demethylation of specific NF-kappaB-responsive enhancer elements and the activation of iNOS transactivation in human OA chondrocytes was seen which was consistent with the differences in methylation status observed in vivo in normal and human OA cartilage and, importantly, show association with the OA process [59]. The pattern of methylation (hypo-, or hyper-mehylation) have earlier been seen in rheumatoid arthritis synovial fibroblast (RASF) by Nakano et al [60].…”
Section: Epigenetics Underlying Bone Metabolismsupporting
confidence: 70%
“…Here, Takahashi et al showed that increased demethylation of the IL8 promoter in OA chondrocytes correlated with enhanced IL8 expression and that expression was mediated by the activity of C/EBP, AP-1, and NF-κB (96). In addition, demethylation of an NF-κB-responsive enhancer was shown to increase the expression of inducible nitric oxide synthase (iNOS), a gene known to be dysregulated in OA (97). Recent analysis from methylation data of hip OA patients identified that the promoter region of a subset of inflammation-associated genes including IL1α and TNF was hypo-methylated, which further led to increased MMP13 expression in OA chondrocytes through zinc ZIP8-MTF 1 axis (88).…”
Section: Dna Methylation and Demethylation In Chondrocyte Inflammatiomentioning
confidence: 99%